The anodal tDCS over the left posterior parietal cortex enhances attention toward a focus word in a sentence - Minamoto, Takehiro; Azuma, Miyuki; Yaoi, Ken; Ashizuka, Aoi; Mima, Tastuya; Osaka, Mariko; Fukuyama, Hidenao; Osaka, Naoyuki (Frontiers in Human Neuroscience, 2014)
The posterior parietal cortex (PPC) has two attentional functions: top-down attentional control and stimulus-driven attentional processing. Using the focused version of the reading span test (RST), in which the target word to be remembered is the critical word for comprehending a sentence (focused word) or a non-focused word, we examined the effect of tDCS on resolution of distractor interference by the focused word in the non-focus condition (top-down attentional control) and on augmented/shrunk attentional capture by the focused word in both the focus and non-focus conditions (stimulus-driven attentional processing). Participants were divided into two groups: anodal tDCS (atDCS) and cathodal tDCS (ctDCS). Online stimulation was given while participants performed the RST. A post-hoc recognition task was also administered in which three kinds of words were presented: target words in the RST, distractor words in the RST, and novel words. atDCS augmented the effect of the focused word by increasing differences in performance between the focus and non-focus conditions. Such an effect was not observed in the ctDCS group. As for the recognition task, atDCS again produced the augmented effect of the focused words in the distractor recognition. On the other hand, ctDCS brought less recognition of non-focused target words in comparison to sham. The results indicate that atDCS promotes stimulus-driven attentional processing, possibly by affecting neural firing in the inferior parietal regions. In contrast, ctDCS appears to prevent retrieval of less important information from episodic memory, which may require top-down attentional processing.